The Relationship between Indonesian Online Learners’ Learning Strategies and Learner-Instructor Interaction in Massive Open Online Course (MOOC) - Elysa Ratna Astuti; Marco Alexandro; Pupung Purnawarman (Bina Nusantara University, 2017)
This study aimed to expose the Indonesian online learners’ learning strategies used in MOOC and investigated the relationship between the learning strategies and learner-instructor interaction in MOOC. The method employed was quantitative research and used the correlational study. The data for this study were collected from 500 Indonesian online learners (359 females and 141 males) who enrolled in Sekolah TOEFL, one of the MOOCs in Indonesia. This study used translated and modified version of Motivated Strategies for Learning Questionnaire (MSLQ), students’ experience in e-learning questionnaire, and learner-instructor interaction in the online course. The three questionnaires were distributed through an electronic survey site, Google FormTM. The data were analyzed using descriptive statistics and Pearson Product Moment Formula to correlate both learning strategies and learner-instructor interaction. The findings enrich our understanding of learners’ learning strategies that are used in MOOC and reveal the relation of the learning strategies and learner-instructor interaction in MOOC.